Factors Influencing the Successful Isolation and Expansion of Aging Human Mesenchymal Stem Cells - Chong, Pan Pan; Selvaratnam, Lakshmi; Abbas, Azlina Amir; Kamarul, Tunku (De Gruyter, 2018)
Most studies highlight mesenchymal stem cells (MSCs) extracted primarily from bone marrow (BM), very few report the use of peripheral blood (PB), often due to the associated low seeding density and difficulties with extraction techniques. As ageing populations are becoming more predominant globally, together with escalating demands for MSC transplantation and tissue regeneration, obtaining quality MSCs suitable for induced differentiation and biological therapies becomes increasingly important. In this study, BM and PB were obtained from elderly patients and extracted MSCs grown in vitro to determine their successful isolation and expansion. Patients' socio-demographic background and other medical information were obtained from medical records. Successful and failed cultures were correlated with key demographic and medical parameters. A total of 112 samples (BM or PB) were used for this study. Of these, 50 samples (44.6%) were successfully cultured according to standardised criteria with no signs of contamination. Our comparative analyses demonstrated no statistical correlation between successful MSC cultures and any of the six demographic or medical parameters examined, including sample quantity, age, sex, race, habits and underlying comorbidities of sample donors. In conclusion, the present study demonstrates that typical demographics and comorbidities do not influence successful MSC isolation and expansion in culture.